Method of Tahqiq al-Manat: A study of its application in the resolutions of al Rajhi Bank Shariah Board / Khaled Mohamad Abdullah - Khaled Mohamad , Abdullah (2018)
Method of tahqiq al-manat is considered as a primary approach to issue fatwas in general, and fatwas on contemporary issues in particular as well as to apply it in the practical reality. This research as entitled (Method of Tahqiq al-Manat: A Study of Its Application in the Resolutions of Al-Rajihi Bank Shariah Board) aims to analyze the approaches of shariah scholars in relation to the concept of tahqiq al-manat. Furthermore, it examines the categories of tahqiq al-manat in accordance with the related association. This research will then conduct the applied study by describing manhajiyat of tahqiq al-manat in al-Rajihi Bank, and studying its application along with stating its impact. The research has been based on the inductive and critical methods as well as descriptive and analitical methods. This research has reached several findings most notably; tahqiq al-manat is a type of ijtihad to prove the subject matter of the shariah ruling as detected by shariah’s evidence; and that the routes of tahqiq al-manat can be divided accordingly to its relevance, i.e. what is related to the fatwa shall be included under the category of evidences of Shariah; and what is related to jurisdiction shall be classified under the routes of al-hijaj (methods of investigating and verifying the issue and the ruling); and what is related in uncovering the reality and its truth shall be classified under the approaches of occurrence evidences. Furthermore, the experts of tahqiq almanat are bound to the approaches of tahqiq al-manat. For example the approaches of the evidences provision’ to achieve al-Manat will be carried out by the legislator, mujtahid and mufti. As for the approaches of al-hijaj in verifying al-manat, it will be carried out by the judge. While the approaches of al-wuqu’ (occurrence) evidences to achieve al-manat it will be carried out by those are addressed to such as the expert, the ummah, the ruler, al-mukallaf, al-muqallid and the commoner uncovering the reality and carrying out and applying the provisions. Tahqiq al-manat has its owm impacts, i.e. renewing the ijtihad, stopping legal rulings and its suspension, disagreement among scholars, mistakes in the fatwa if it breaches its correct methodology. Among other findings of the applied study, the research has reached that the muhaqiqi al-manat in the approaches of the shariah evidence in al- Rajihi Bank are the Shariah board, the shariah committee and the shariah working team. As for the approaches of the al-hijaj, they are represented in the shariah courts and by what is determined by the general rules in jurisdiction and by the Committee for Settlement of Bank Disputes. In al-wuqu’ (occurance) evidence approaches, it is done by the ruler or its representative and the company executive administration at all levels. The Shariah Committee relied on the various provisions’ evidence approaches based on al-Quran al-Sunnah, alqiyas, al-Ijma’ and al-bara’a al-asliyyah, the companion’s statement and mujtahidin without restriction to a specific madhhab (school of thought) and Fiqh Council resolutions. By applied study it became clear that tahqiq al-manat has an impact on the fatwa diversity, even within one Shariah board itself, and also it has an impact on ijtihad renewal and possibility of fatwa mistakes. In order to overcome this scenario, there must be an extensive study on such raised issues involving experts in the related fields and Muslim jurists as well as to rely on one unified standards.